Pengembangan Sistem Aplikasi Penjadwalan Dosen Jurusan Teknik Mesin Politeknik Negeri Malang berbasis Web - Austenita Pasca Aisyah; Bayu Priyambadha; Arief Andy Soebroto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The educational institutions cannot be separated from scheduling activities because it helps the learning activities to be run properly. However, there are times when scheduling can cause problems such as the clash of the teaching schedule of a lecturer that happened in the Mechanical Engineering Department of Politeknik Negeri Malang (JTM POLINEMA). The manually-done scheduling process by each JTM POLINEMA's Head of the Study Program (KPS) is the reason that the learning activities have to be delayed up to one week. Therefore, this study aims to assist the work of KPS in arranging lecturers' schedules by designing and developing a web-based scheduling system that helps minimize human errors in scheduling and facilitating the schedules' distribution for each lecturer. The development of this system consists of requirement analysis, design, implementation, and system testing. This application system is designed using an object-oriented (OOP) approach and waterfall software development model and will be implemented using the PHP programming language. For testing, this system will be tested with whitebox testing, blackbox testing, and compatibility testing. The results of this study are 100% valid in unit testing, 97.5% valid in validation testing, and the system can work properly on Mozilla Firefox and Google Chrome.